2013
DOI: 10.1002/bip.22194
|View full text |Cite
|
Sign up to set email alerts
|

An interplay between electrostatic and polar interactions in peptide hydrogels

Abstract: Inherent chemical programmability available in peptide-based hydrogels has allowed diversity in the development of these materials for use in biomedical applications. Within the 20 natural amino acids, a range of chemical moieties are present. Here we used a mixing-induced self-assembly of two oppositely charged peptide modules to form a peptide-based hydrogel. To investigate electrostatic and polar interactions on the hydrogel, we replace amino acids from the negatively charged acidic glutamic acid (E) to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…For example, it is difficult to choose the length of the alkyl chain, [9b] too many aromatic groups may inhibit cells in some cases, [4,12] too strong charge interactions results in poor reversibility. [13] Thus, it is necessary and beneficial to explore new strategies to complement the existing ones for supramolecular hydrogels.…”
mentioning
confidence: 99%
“…For example, it is difficult to choose the length of the alkyl chain, [9b] too many aromatic groups may inhibit cells in some cases, [4,12] too strong charge interactions results in poor reversibility. [13] Thus, it is necessary and beneficial to explore new strategies to complement the existing ones for supramolecular hydrogels.…”
mentioning
confidence: 99%
“…Larger L c corresponds to larger spatial extent of the cross-linking fibrous regions. 35 L c has been explored and successfully applied to understand the effects of ionic strength 36 and electrostatic interactions 37 on the structural characteristics of peptide-based hydrogels.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of salt bridges affects the formation of fibrous and porous peptide based scaffolds that are rich in β‐sheet secondary structure . Electrostatic interferences are induced by salts, ions, macromolecules, and pH changes . The effect of salt concentration on sol–gel transition in solutions containing amphiphilic peptides has been studied, and it was found that amphiphilic peptide solutions with higher salt concentrations have higher gelation rates and mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Electrostatic interferences are induced by salts, ions, macromolecules, and pH changes. [15][16][17] The effect of salt concentration on sol-gel transition in solutions containing amphiphilic peptides has been studied, and it was found that amphiphilic peptide solutions with higher salt concentrations have higher gelation rates and mechanical properties. 18,19 Rheological studies are necessary to compare different conditions of peptides.…”
Section: Introductionmentioning
confidence: 99%